Preparation method of long-acting stable dust suppressant

By modifying the polyacrylamide in the dust suppressor and adding a composite cross-linking agent, a cross-linked interpenetrating network structure is formed, which solves the problem of reduced dust suppression effect of existing dust suppressants after long-term use and achieves long-term stability. and improved wind resistance.

CN119351057AInactive Publication Date: 2025-01-24INNER MONGOLIA HAITAI ENERGY SAVING & ENVIRONMENTAL PROTECTION ENG CO LTD

Patent Information

Application Number
CN202411918680.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

After long-term use of existing dust inhibitors, the dust suppression effect is greatly reduced, and they cannot have a long-term good dust suppression effect in the material yard.

Method used

By modifying the polyacrylamide in the dust suppressant and adding a composite cross-linking agent, it forms a cross-linked interpenetrating network structure during the spray curing process, improving its wind resistance and stability.

Benefits of technology

The preparation of long -term stable dust suppression agents has a good wind resistance effect, and it can still maintain good dust suppression effect after long -term use.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of dust suppressants, in particular to a preparation method of a long-acting stable dust suppressant, which is prepared from the following raw materials in parts by weight: 8 to 10 parts of modified polyacrylamide, 0.5 to 1 part of composite cross-linking agent, 0.8 to 1 part of sodium polyacrylate, 1 to 1.2 parts of gum arabic, 0.8 to 1 part of xanthan gum, 2 to 2.5 parts of water-retaining agent, 1 to 1.2 parts of surfactant and 800 to 850 parts of water. Polyacrylamide in the dust suppressant is modified, and the composite curing agent is added, so that a cross-linked interpenetrating network structure is formed in the spraying and curing process, the wind-resistant dust suppressant has a good wind-resistant effect, and the problem that the dust suppression effect is greatly reduced after an existing dust suppressant is used for a long time is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dust suppressants, and in particular to a method for preparing a long-acting stable dust suppressant. Background Art

[0002] In the process of construction industry production operations, material yards, ore mining and road transportation, it is very easy to generate a large amount of dust due to wind, which leads to waste of resources and environmental damage. At present, watering method, cloth covering method, chemical dust suppressant method, etc. are usually chosen. Among them, chemical dust suppressants have the advantages of good dust suppression effect and long dust suppression cycle. However, most dust suppressants have poor long-term stability and cannot play a long-term good dust suppression effect in material yards. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a long-acting stable dust suppressant. By modifying the polyacrylamide in the dust suppressant and adding a composite curing agent, a cross-linked interpenetrating network structure is formed during the spraying and curing process. The structure has good wind resistance and solves the problem that the dust suppression effect of the existing dust suppressant is greatly reduced after long-term use.

[0004] The object of the present invention can be achieved by the following technical scheme: A method for preparing a long-acting stable dust suppressant, comprising the following steps: Step S1: weighing the following raw materials in parts by weight: 8-10 parts of modified polyacrylamide, 0.5-1 parts of a composite cross-linking agent, 0.8-1 parts of sodium polyacrylate, 1-1.2 parts of gum arabic, 0.8-1 parts of xanthan gum, 2-2.5 parts of a water retaining agent, 1-1.2 parts of a surfactant and 800-850 parts of water; Step S2: mixing modified polyacrylamide, sodium polyacrylate, gum arabic, xanthan gum, a water retaining agent, a surfactant and water, stirring and adding a composite cross-linking agent to prepare a long-acting stable dust suppressant; The modified polyacrylamide is prepared by the following steps: Step A1: Mix rosin, tetrabutylammonium bromide and anhydrous ethanol, stir at a rate of 120-140 rpm and a temperature of 80° C., add epichlorohydrin, and react for 3-5 hours to obtain intermediate 1; mix intermediate 1, N-methyldiallylamine, p-hydroxyanisole and anhydrous ethanol, stir at a rate of 120-140 rpm and a temperature of 65° C., and react for 24 hours to obtain intermediate 2; The dosage ratio of rosin, tetrabutylammonium bromide and epichlorohydrin is 9.06-9.14g:0.014-0.15g:0.042-0.045mol; the dosage ratio of intermediate 1, triallylamine and p-hydroxyanisole is 9.35-9.45g:0.038-0.042mol:0.05-0.06g; During the reaction, under the action of tetrabutylammonium bromide, the carboxyl group in rosin reacts with the epoxy group in epichlorohydrin to introduce chlorine to obtain intermediate 1, and then under the action of p-hydroxyanisole, the chlorine in intermediate 1 reacts with the tertiary amine group in triallylamine to form a quaternary ammonium structure, and a terminal double bond is introduced to obtain intermediate 2; Step A2: lipoic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dichloromethane are mixed, stirred at a stirring rate of 50-60 rpm and room temperature, 2-hydroxyethyl methacrylate is added, and the reaction is carried out for 12-14 hours to obtain intermediate 3; intermediate 2, acrylamide, N-isopropylacrylamide and deionized water are mixed, stirred at a stirring rate of 120-130 rpm and a temperature of 70° C., azobisisobutyramidine hydrochloride is added, the reaction is carried out for 4-6 hours, the temperature is lowered to 50° C., intermediate 3 is added, and the reaction is continued for 2-3 hours to obtain modified polyacrylamide; The amount ratio of lipoic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 2-hydroxyethyl methacrylate is 0.02-0.03 mol: 5.2-5.5 g: 8.4-8.6 g: 0.024-0.034 mol; the amount ratio of intermediate 2, acrylamide, N-isopropylacrylamide, azobisisobutyramidine hydrochloride and intermediate 3 is 6.5-6.8 g: 0.3-0.4 mol: 0.2-0.3 mol: 0.05-0.06 mol; During the reaction, the carboxyl group in lipoic acid reacts with the hydroxyl group in 2-hydroxyethyl methacrylate under the action of 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide to introduce a double bond to obtain intermediate 3, and then under the action of an initiator azobisisobutyramidine hydrochloride, free radical polymerization occurs among the double bonds in intermediate 2, acrylamide, N-isopropylacrylamide and intermediate 3 to obtain modified polyacrylamide; The composite cross-linking agent is prepared by the following steps: Step B1: 2,2'-disulfide dipyridine and dichloromethane are mixed, stirred at a stirring rate of 120-140 rpm and room temperature, 3-mercaptopropyltriethoxysilane is added, and the mixture is reacted for 24 hours to obtain modified silane, short-cut alumina fibers, modified silane and ethanol solution are mixed and ultrasonically dispersed for 15 minutes, and the mixture is reacted for 1.5-2 hours at a stirring rate of 120-130 rpm and a temperature of 75°C to obtain modified alumina fibers; The dosage ratio of 2,2'-disulfide dipyridine and 3-mercaptopropyl triethoxysilane is 0.2-0.21 mol: 0.42-0.44 mol; the volume fraction of the ethanol solution is 30%, and the dosage ratio of the chopped alumina fiber and the modified silane is 1.6-1.8 g: 0.08-0.1 g; During the reaction, since 2,2'-disulfide pyridine contains a disulfide bond, it can condense with the mercapto group in 3-mercaptopropyltriethoxysilane, thereby introducing a disulfide bond and a pyridine group into the silane to obtain a modified silane. The silicon ethoxy group in the modified silane is hydrolyzed in an ethanol solution and grafted onto the short-cut alumina fiber to obtain a modified alumina fiber. Step B2: zirconium chloride, hydrochloric acid solution and N,N-dimethylformamide are mixed, and 2-aminoterephthalic acid and modified alumina fiber are added under stirring conditions of a stirring rate of 100-120 rpm and a temperature of 110° C., and the mixture is reacted for 24 hours to obtain composite alumina fiber; The mass fraction of the hydrochloric acid solution is 20%, and the dosage ratio of zirconium chloride, hydrochloric acid solution, 2-aminoterephthalic acid and modified alumina fiber is 0.75-0.8g: 0.4-0.5mL: 0.85-0.92g: 0.6-0.64g; During the reaction, a metal organic framework structure is formed by a solvent thermal method with zirconium chloride as a zirconium source and 2-aminoterephthalic acid as a ligand. Since the surface of the modified alumina fiber is grafted with pyridine groups, the metal organic framework is attached to the modified alumina fiber to obtain a composite alumina fiber. Step B3: the composite alumina fiber and dichloromethane are mixed and ultrasonically dispersed, the reaction is carried out for 24 hours at a stirring rate of 180-200 rpm and room temperature, and methacrylic anhydride is added to prepare a composite crosslinking agent while stirring; The ratio of composite alumina fiber to methacrylic anhydride is 0.5-0.54 g: 0.5-0.6 mL; During the reaction, the amino groups on the 2-aminoterephthalic acid in the metal organic framework structure of the composite alumina fiber react with the anhydride groups in the methacrylic anhydride, thereby introducing double bonds to prepare a composite crosslinking agent. Beneficial effects of the invention: The invention discloses a method for preparing a long-acting stable dust suppressant. The polyacrylamide in the dust suppressant is modified and a composite curing agent is added to form a cross-linked interpenetrating network structure during the spraying and curing process. The structure has good wind resistance and solves the problem that the dust suppression effect of the existing dust suppressant is greatly reduced after long-term use. The modified polyacrylamide is prepared with intermediate 2, intermediate 3, acrylamide and N-isopropylacrylamide as monomers. Due to the triallylamine structure of intermediate 2, a branched structure is formed after polymerization. At the same time, due to the ring opening of the thioctic acid structure contained in the intermediate, the structure undergoes self-polymerization or a click reaction with a composite cross-linking agent containing double bonds, thereby forming a cross-linked interpenetrating network structure. The structure can greatly improve the stability after curing and film formation. The composite cross-linking agent itself is a metal organic skeleton attached to short-cut alumina fibers as a substrate, which can be used as a stress node to improve the compressive strength after film formation. At the same time, this structure can also be combined with modified polyacrylamide containing rosin groups, so that the cured film is firmly fixed on the surface of the material, thereby greatly improving the stability and wind resistance of the dust suppressant. DETAILED DESCRIPTION

[0005] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0006] Example 1 A method for preparing a long-acting stable dust suppressant comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 8 parts of modified polyacrylamide, 0.5 parts of a composite cross-linking agent, 0.8 parts of commercially available Shuangcheng 0687 sodium polyacrylate, 1 part of commercially available Runtai gum arabic, 0.8 parts of commercially available Mingtong xanthan gum, 2 parts of commercially available Qimai CA-20 water retaining agent, 1 part of commercially available CP12S surfactant and 800 parts of water; Step S2: mixing modified polyacrylamide, sodium polyacrylate, gum arabic, xanthan gum, a water retaining agent, a surfactant and water, stirring and adding a composite cross-linking agent to prepare a long-acting stable dust suppressant; The modified polyacrylamide is prepared by the following steps: Step A1: Mix commercially available Wanshan New Materials rosin, tetrabutylammonium bromide and anhydrous ethanol, stir at a stirring rate of 120 rpm and a temperature of 80°C, add epichlorohydrin, and react for 3 hours to obtain intermediate 1; mix intermediate 1, N-methyldiallylamine, p-hydroxyanisole and anhydrous ethanol, and react at a stirring rate of 120 rpm and a temperature of 65°C for 24 hours to obtain intermediate 2; The ratio of rosin, tetrabutylammonium bromide and epichlorohydrin is 9.06g:0.014g:0.042mol; the ratio of intermediate 1, triallylamine and p-hydroxyanisole is 9.35g:0.038mol:0.05g; Step A2: lipoic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dichloromethane were mixed, stirred at a stirring rate of 50 rpm and room temperature, and 2-hydroxyethyl methacrylate was added, and the reaction was continued for 12 hours to obtain intermediate 3; intermediate 2, acrylamide, N-isopropylacrylamide and deionized water were mixed, stirred at a stirring rate of 120 rpm and a temperature of 70°C, azobisisobutyramidine hydrochloride was added, the reaction was continued for 4 hours, the temperature was lowered to 50°C, intermediate 3 was added, and the reaction was continued for 2 hours to obtain modified polyacrylamide; The amount ratio of lipoic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 2-hydroxyethyl methacrylate is 0.02 mol: 5.2 g: 8.4 g: 0.024 mol; the amount ratio of intermediate 2, acrylamide, N-isopropylacrylamide, azobisisobutyramidine hydrochloride and intermediate 3 is 6.5 g: 0.3 mol: 0.2 mol: 0.05 mol; The composite cross-linking agent is prepared by the following steps: Step B1: 2,2'-disulfide dipyridine and dichloromethane were mixed, stirred at a stirring rate of 120 rpm and room temperature, and 3-mercaptopropyltriethoxysilane was added, and the reaction was carried out for 24 hours to obtain modified silane. Commercially available Rongbang chopped alumina fibers, modified silane and ethanol solution were mixed and ultrasonically dispersed for 15 minutes, and the reaction was carried out for 1.5 hours at a stirring rate of 120 rpm and a temperature of 75°C to obtain modified alumina fibers; The ratio of 2,2'-disulfide dipyridine to 3-mercaptopropyltriethoxysilane is 0.2 mol:0.42 mol; the volume fraction of the ethanol solution is 30%, and the ratio of chopped alumina fiber to modified silane is 1.6 g:0.08 g; Step B2: zirconium chloride, hydrochloric acid solution and N,N-dimethylformamide were mixed, and 2-aminoterephthalic acid and modified alumina fiber were added under stirring conditions of a stirring rate of 100 rpm and a temperature of 110° C., and the mixture was reacted for 24 hours to obtain composite alumina fiber; The mass fraction of the hydrochloric acid solution is 20%, and the dosage ratio of zirconium chloride, hydrochloric acid solution, 2-aminoterephthalic acid and modified alumina fiber is 0.75g: 0.4mL: 0.85g: 0.6g; Step B3: the composite alumina fiber and dichloromethane are mixed and ultrasonically dispersed, the reaction is carried out for 24 hours at a stirring rate of 180 rpm and room temperature, and methacrylic anhydride is added to prepare a composite crosslinking agent while stirring; The usage ratio of composite alumina fiber and methacrylic anhydride is 0.5 g:0.5 mL.

[0007] Example 2 A method for preparing a long-lasting stable dust suppressant comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 10 parts of modified polyacrylamide, 1 part of a composite cross-linking agent, 1 part of commercially available Shuangcheng 0687 sodium polyacrylate, 1 part of commercially available Runtai gum arabic, 0.8 parts of commercially available Mingtong xanthan gum, 2.5 parts of commercially available Qimai CA-20 water retaining agent, 1.2 parts of commercially available CP12S surfactant and 850 parts of water; Step S2: mixing modified polyacrylamide, sodium polyacrylate, gum arabic, xanthan gum, a water retaining agent, a surfactant and water, stirring and adding a composite cross-linking agent to prepare a long-acting stable dust suppressant; The modified polyacrylamide is prepared by the following steps: Step A1: Mix commercially available Wanshan New Materials rosin, tetrabutylammonium bromide and anhydrous ethanol, stir at a stirring rate of 120 rpm and a temperature of 80°C, add epichlorohydrin, and react for 5 hours to obtain intermediate 1; mix intermediate 1, N-methyldiallylamine, p-hydroxyanisole and anhydrous ethanol, and react at a stirring rate of 120 rpm and a temperature of 65°C for 24 hours to obtain intermediate 2; The ratio of rosin, tetrabutylammonium bromide and epichlorohydrin is 9.14g:0.014g:0.045mol; the ratio of intermediate 1, triallylamine and p-hydroxyanisole is 9.35g:0.042mol:0.06g; Step A2: lipoic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dichloromethane were mixed, stirred at a stirring rate of 50 rpm and room temperature, and 2-hydroxyethyl methacrylate was added, and the reaction was continued for 14 hours to obtain intermediate 3; intermediate 2, acrylamide, N-isopropylacrylamide and deionized water were mixed, stirred at a stirring rate of 120 rpm and a temperature of 70°C, azobisisobutyramidine hydrochloride was added, the reaction was continued for 6 hours, the temperature was lowered to 50°C, intermediate 3 was added, and the reaction was continued for 2-3 hours to obtain modified polyacrylamide; The amount ratio of lipoic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 2-hydroxyethyl methacrylate is 0.02 mol: 5.5 g: 8.4 g: 0.034 mol; the amount ratio of intermediate 2, acrylamide, N-isopropylacrylamide, azobisisobutyramidine hydrochloride and intermediate 3 is 6.8 g: 0.3 mol: 0.3 mol: 0.05 mol; The composite cross-linking agent is prepared by the following steps: Step B1: 2,2'-disulfide dipyridine and dichloromethane were mixed, stirred at a stirring rate of 120 rpm and room temperature, and 3-mercaptopropyltriethoxysilane was added, and the reaction was carried out for 24 hours to obtain modified silane. Commercially available Rongbang chopped alumina fibers, modified silane and ethanol solution were mixed and ultrasonically dispersed for 15 minutes, and the reaction was carried out for 2 hours at a stirring rate of 120 rpm and a temperature of 75°C to obtain modified alumina fibers; The ratio of 2,2'-disulfide dipyridine to 3-mercaptopropyltriethoxysilane is 0.2 mol:0.44 mol; the volume fraction of the ethanol solution is 30%, and the ratio of chopped alumina fiber to modified silane is 1.6 g:0.1 g; Step B2: zirconium chloride, hydrochloric acid solution and N,N-dimethylformamide were mixed, and 2-aminoterephthalic acid and modified alumina fiber were added under stirring conditions of a stirring rate of 120 rpm and a temperature of 110° C., and the mixture was reacted for 24 hours to obtain composite alumina fiber; The mass fraction of the hydrochloric acid solution is 20%, and the dosage ratio of zirconium chloride, hydrochloric acid solution, 2-aminoterephthalic acid and modified alumina fiber is 0.75g: 0.5mL: 0.85g: 0.64g; Step B3: the composite alumina fiber and dichloromethane are mixed and ultrasonically dispersed, the reaction is carried out for 24 hours at a stirring rate of 180 rpm and room temperature, and methacrylic anhydride is added to prepare a composite crosslinking agent while stirring; The usage ratio of composite alumina fiber and methacrylic anhydride is 0.5 g:0.6 mL.

[0008] Example 3 A method for preparing a long-lasting stable dust suppressant comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 10 parts of modified polyacrylamide, 1 part of a composite cross-linking agent, 1 part of commercially available Shuangcheng 0687 sodium polyacrylate, 1.2 parts of commercially available Runtai gum arabic, 1 part of commercially available Mingtong xanthan gum, 2.5 parts of commercially available Qimai CA-20 water retaining agent, 1.2 parts of commercially available CP12S surfactant and 850 parts of water; Step S2: mixing modified polyacrylamide, sodium polyacrylate, gum arabic, xanthan gum, a water retaining agent, a surfactant and water, stirring and adding a composite cross-linking agent to prepare a long-acting stable dust suppressant; The modified polyacrylamide is prepared by the following steps: Step A1: Mix commercially available Wanshan New Materials rosin, tetrabutylammonium bromide and anhydrous ethanol, stir at a stirring rate of 140 rpm and a temperature of 80°C, add epichlorohydrin, and react for 5 hours to obtain intermediate 1; mix intermediate 1, N-methyldiallylamine, p-hydroxyanisole and anhydrous ethanol, and react at a stirring rate of 140 rpm and a temperature of 65°C for 24 hours to obtain intermediate 2; The dosage ratio of rosin, tetrabutylammonium bromide and epichlorohydrin is 9.14g:0.15g:0.045mol; the dosage ratio of intermediate 1, triallylamine and p-hydroxyanisole is 9.35-9.45g:0.042mol:0.06g; Step A2: lipoic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dichloromethane were mixed, stirred at a stirring rate of 60 rpm and room temperature, and 2-hydroxyethyl methacrylate was added, and the reaction was continued for 12-14 hours to obtain intermediate 3; intermediate 2, acrylamide, N-isopropylacrylamide and deionized water were mixed, stirred at a stirring rate of 130 rpm and a temperature of 70°C, azobisisobutyramidine hydrochloride was added, the reaction was continued for 6 hours, the temperature was lowered to 50°C, intermediate 3 was added, and the reaction was continued for 3 hours to obtain modified polyacrylamide; The amount ratio of lipoic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 2-hydroxyethyl methacrylate is 0.03 mol: 5.5 g: 8.6 g: 0.034 mol; the amount ratio of intermediate 2, acrylamide, N-isopropylacrylamide, azobisisobutyramidine hydrochloride and intermediate 3 is 6.8 g: 0.4 mol: 0.3 mol: 0.06 mol; The composite cross-linking agent is prepared by the following steps: Step B1: 2,2'-disulfide dipyridine and dichloromethane were mixed, stirred at a stirring rate of 140 rpm and room temperature, and 3-mercaptopropyltriethoxysilane was added, and the mixture was reacted for 24 hours to obtain modified silane. Commercially available Rongbang chopped alumina fibers, modified silane and ethanol solution were mixed and ultrasonically dispersed for 15 minutes, and the mixture was reacted for 2 hours at a stirring rate of 130 rpm and a temperature of 75°C to obtain modified alumina fibers. The ratio of 2,2'-disulfide dipyridine to 3-mercaptopropyltriethoxysilane is 0.21 mol:0.44 mol; the volume fraction of the ethanol solution is 30%, and the ratio of chopped alumina fiber to modified silane is 1.8 g:0.1 g; Step B2: zirconium chloride, hydrochloric acid solution and N,N-dimethylformamide were mixed, and 2-aminoterephthalic acid and modified alumina fiber were added under stirring conditions of a stirring rate of 120 rpm and a temperature of 110° C., and the mixture was reacted for 24 hours to obtain composite alumina fiber; The mass fraction of the hydrochloric acid solution is 20%, and the dosage ratio of zirconium chloride, hydrochloric acid solution, 2-aminoterephthalic acid and modified alumina fiber is 0.8g: 0.5mL: 0.92g: 0.64g; Step B3: the composite alumina fiber and dichloromethane are mixed and ultrasonically dispersed, the reaction is carried out for 24 hours at room temperature with a stirring rate of 200 rpm, and methacrylic anhydride is added to obtain a composite crosslinking agent by stirring; The usage ratio of composite alumina fiber and methacrylic anhydride is 0.54 g:0.6 mL.

[0009] Comparative Example 1 Compared with Example 3, this comparative example is characterized in that triallylamine in the preparation process of modified polyacrylamide in Example 3 is replaced by N-methyldiallylamine, and the other steps are the same.

[0010] Comparative Example 2 Compared with Example 3, this comparative example is characterized in that the lipoic acid in the preparation process of the modified polyacrylamide in Example 3 is replaced by octanoic acid, and the other steps are the same.

[0011] Comparative Example 3 Compared with Example 3, this comparative example is different in that the composite cross-linking agent in the preparation process of the long-acting stable dust suppressant in Example 3 is replaced by short-cut alumina fibers, and the other steps are the same.

[0012] Take the long-acting stable dust suppressant prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, place the coal powder in a container and spray the long-acting temperature dust suppressant on the surface, the spraying amount is 0.4L / m 2 , cured at room temperature for 24 hours, fixed in a climate box, and tested for water penetration resistance. The spraying time was 10 minutes, the spraying intensity was 12 mm / min, and its moisture content was calculated to determine its rain penetration resistance. A wind fan was used for wind resistance test at a wind speed of 20 m / s, and its wind erosion rate was calculated. It was placed under ultraviolet light and a temperature of 30°C, aged for 30 days, and tested for water penetration resistance and wind resistance again. The test results are as follows: Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Water content (g / cm 2 )]]> 0.135 0.129 0.127 0.264 0.164 0.193 Wind erosion rate (%) 6.564 6.488 6.472 8.075 7.552 7.841 <![CDATA[Water content after aging (g / cm 2 )]]> 0.275 0.269 0.261 0.519 0.359 0.409 Wind erosion rate after aging (%) 9.027 8.982 8.953 12.318 10.170 11.260 It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2 and Comparative Example 3, Comparative Example 1 replaces the triallylamine in the preparation process of the modified polyacrylamide in Example 3 with N-methyldiallylamine, and its performance is reduced due to the lack of a branched structure. Comparative Example 2 replaces the thioctic acid in the preparation process of the modified polyacrylamide in Example 3 with octanoic acid, and its performance is reduced due to the lack of a click reaction between the modified polyacrylamide and the composite cross-linking agent. Comparative Example 3 replaces the composite cross-linking agent in the preparation process of the long-acting stable dust suppressant in Example 3 with chopped alumina fibers, and its performance is reduced.

[0013] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0014] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a long-acting stable dust suppressant, characterized in that: The method comprises the following steps: Step S1: weighing the following raw materials in parts by weight: 8-10 parts of modified polyacrylamide, 0.5-1 parts of composite cross-linking agent, 0.8-1 parts of sodium polyacrylate, 1-1.2 parts of gum arabic, 0.8-1 parts of xanthan gum, 2-2.5 parts of water retaining agent, 1-1.2 parts of surfactant and 800-850 parts of water; Step S2: Modified polyacrylamide, sodium polyacrylate, gum arabic, xanthan gum, water retaining agent, surfactant and water are mixed, stirred and a composite cross-linking agent is added to prepare a long-acting stable dust suppressant.

2. The method for preparing a long-acting stable dust suppressant according to claim 1, characterized in that: The modified polyacrylamide is prepared by the following steps: Step A1: Mix rosin, tetrabutylammonium bromide and anhydrous ethanol, stir at a rate of 120-140 rpm and a temperature of 80° C., add epichlorohydrin, and react for 3-5 hours to obtain intermediate 1; mix intermediate 1, N-methyldiallylamine, p-hydroxyanisole and anhydrous ethanol, stir at a rate of 120-140 rpm and a temperature of 65° C., and react for 24 hours to obtain intermediate 2; Step A2: lipoic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dichloromethane are mixed, stirred at a stirring rate of 50-60 rpm, at room temperature, 2-hydroxyethyl methacrylate is added, and the reaction is carried out for 12-14 hours to obtain intermediate 3; intermediate 2, acrylamide, N-isopropylacrylamide and deionized water are mixed, stirred at a stirring rate of 120-130 rpm, at a temperature of 70°C, azobisisobutyramidine hydrochloride is added, the reaction is carried out for 4-6 hours, the temperature is lowered to 50°C, intermediate 3 is added, and the reaction is continued for 2-3 hours to obtain modified polyacrylamide.

3. The method for preparing a long-acting stable dust suppressant according to claim 2, characterized in that: In step A1, the ratio of rosin, tetrabutylammonium bromide and epichlorohydrin is 9.06-9.14 g: 0.014-0.15 g: 0.042-0.045 mol; the ratio of intermediate 1, triallylamine and p-hydroxyanisole is 9.35-9.45 g: 0.038-0.042 mol: 0.05-0.06 g.

4. The method for preparing a long-acting stable dust suppressant according to claim 2, characterized in that: In step A2, the amount ratio of lipoic acid, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 2-hydroxyethyl methacrylate is 0.02-0.03 mol: 5.2-5.5 g: 8.4-8.6 g: 0.024-0.034 mol; the amount ratio of intermediate 2, acrylamide, N-isopropylacrylamide, azobisisobutyramidine hydrochloride and intermediate 3 is 6.5-6.8 g: 0.3-0.4 mol: 0.2-0.3 mol: 0.05-0.06 mol.

5. The method for preparing a long-acting stable dust suppressant according to claim 1, characterized in that: The composite cross-linking agent is prepared by the following steps: Step B1: 2,2'-disulfide dipyridine and dichloromethane are mixed, stirred at a stirring rate of 120-140 rpm and room temperature, 3-mercaptopropyltriethoxysilane is added, and the mixture is reacted for 24 hours to obtain modified silane, short-cut alumina fibers, modified silane and ethanol solution are mixed and ultrasonically dispersed for 15 minutes, and the mixture is reacted for 1.5-2 hours at a stirring rate of 120-130 rpm and a temperature of 75°C to obtain modified alumina fibers; Step B2: zirconium chloride, hydrochloric acid solution and N,N-dimethylformamide are mixed, and 2-aminoterephthalic acid and modified alumina fiber are added under stirring conditions of a stirring rate of 100-120 rpm and a temperature of 110° C., and the mixture is reacted for 24 hours to obtain composite alumina fiber; Step B3: The composite alumina fiber and dichloromethane are mixed and ultrasonically dispersed, and the mixture is reacted for 24 hours at room temperature at a stirring rate of 180-200 rpm, and methacrylic anhydride is added thereto to prepare a composite crosslinking agent.

6. The method for preparing a long-acting stable dust suppressant according to claim 5, characterized in that: In step B1: the ratio of 2,2'-disulfide dipyridine to 3-mercaptopropyltriethoxysilane is 0.2-0.21 mol: 0.42-0.44 mol; the volume fraction of the ethanol solution is 30%, and the ratio of chopped alumina fiber to modified silane is 1.6-1.8 g: 0.08-0.1 g.

7. The method for preparing a long-acting stable dust suppressant according to claim 5, characterized in that: In step B2: the mass fraction of the hydrochloric acid solution is 20%, and the dosage ratio of zirconium chloride, hydrochloric acid solution, 2-aminoterephthalic acid and modified alumina fiber is 0.75-0.8g: 0.4-0.5mL: 0.85-0.92g: 0.6-0.64g.

8. The method for preparing a long-acting stable dust suppressant according to claim 5, characterized in that: In step B3: the ratio of composite alumina fiber to methacrylic anhydride is 0.5-0.54 g: 0.5-0.6 mL.

Citation Information

Patent Citations

  • Dust suppressant

    CN108977174A

  • Environment-friendly degradable composite dust suppressant and preparation method thereof

    CN118956348A

  • Dust suppressant for minerals

    US4981398A

Cited By

  • Formula and application of long-acting high-molecular polymer dust suppressant

    CN120536112A